2019
DOI: 10.1093/bib/bby127
|View full text |Cite
|
Sign up to set email alerts
|

ANPELA: analysis and performance assessment of the label-free quantification workflow for metaproteomic studies

Abstract: Label-free quantification (LFQ) with a specific and sequentially integrated workflow of acquisition technique, quantification tool and processing method has emerged as the popular technique employed in metaproteomic research to provide a comprehensive landscape of the adaptive response of microbes to external stimuli and their interactions with other organisms or host cells. The performance of a specific LFQ workflow is highly dependent on the studied data. Hence, it is essential to discover the most appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(43 citation statements)
references
References 144 publications
1
42
0
Order By: Relevance
“…By selecting the top‐ranked genes (top 100 as frequently applied and widely accepted in DEGs study), a variety of signatures were identified by the Student's t test (Table S3) and SAM (Table S4). The CS values have been frequently used for quantitative evaluation on the consistency among the signatures discovered from multiple independent datasets . Therefore, based on the signatures identified from nine independent datasets, the CS for each method was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…By selecting the top‐ranked genes (top 100 as frequently applied and widely accepted in DEGs study), a variety of signatures were identified by the Student's t test (Table S3) and SAM (Table S4). The CS values have been frequently used for quantitative evaluation on the consistency among the signatures discovered from multiple independent datasets . Therefore, based on the signatures identified from nine independent datasets, the CS for each method was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…By combining multiple weak classifiers, the final results can be voted or averaged to obtain an overall model with higher accuracy, better general performance, and resistance to overfitting. This algorithm has been extensively used in bioinformatics and other areas, and has been confirmed to be an effective modeling technique in various domains (Ding et al, 2016a,b;Mrozek et al, 2016;Qiu et al, 2016;Wang et al, 2017;Wei et al, 2017a,b,c;Yu et al, 2017a;Zheng et al, 2017;Tang et al, 2018Tang et al, , 2019aXue et al, 2018;Degenhardt et al, 2019;Xu et al, 2019). In this study, the scikit-learn toolkit, available at https://scikit-learn.org, was used to establish the models.…”
Section: Algorithmmentioning
confidence: 99%
“…CTD features represent the structural or physicochemical distribution patterns of amino acids in protein or peptide sequences (Dubchak et al, 1999;Tang et al, 2020). Thirteen types of physicochemical properties were used to calculate these characteristics, including hydrophobicity, standardized van der Waals volume, solvent accessibility, polarity, secondary structure, polarizability, and charge.…”
Section: Ctdmentioning
confidence: 99%